Mechanical and Water Absorption Characterization of Mango Seed Shell/Epoxy Composite for Low Load Carrying Structures - K. Mohan Kumar; Venkatesh Naik; Sunil S. Waddar; N. Santhosh; Vijayanand Kaup; H. V. Harish (International Journal of Polymer Science)
The present work deals with the characterization of mango seed shell fiber reinforced epoxy composites by using hand layup method by varying the volume composition of the mango seed shell from 0 vol. % to 60 vol. % (M-0 to M-60). The physical density test, tensile test, flexural test, and water absorption test were conducted as per the American Society for Testing and Materials (ASTM) standards. Results revealed that the tensile strength of M-20 (20 vol. %) is 43% more than a neat epoxy, while the flexural strength of M-50 (50 vol. %) is greater than 10.85% more than a neat epoxy. The water absorption test was conducted by immersing the samples in distilled water at room temperature, and the weight of the specimens was measured and recorded at every 24-hour time interval. For all composite samples, saturation in water absorption and thickness swelling were observed after 432 hours of water immersion. The moisture absorption increases with the inclusion of reinforcements as compared to the neat epoxy samples. However, for the M-50 composite, the water absorption decreases due to the uniform mixing and stronger bonding between the matrix and the reinforcements. The scanning electron microscope (SEM) images of the composite specimens also depicted the particulate fiber distribution and the presence of micro-voids in the epoxy matrix.